THE STUDY OF RENOPROTECTIVE PROPERTIES OF ERYTROPOETIN DERIVATIVES ON THE KIDNEY ISCHEMIA-REPERFUSION MODEL - V. V. Elagin; D. A. Kostina; O. I. Bratchikov; M. V. Pokrovsky; T. G. Pokrovskaya (Кубанский научный медицинский вестник, 2018)
Aim. The research was designed to study the renoprotective properties of erythropoietin derivatives on the kidney ischemiareperfusion experimental model.Materials and methods. The renoprotective properties of asialo erythropoietin (0.4 μg/kg and 2.4 μg/kg 30 minutes before the induction of ischemia) and carbamylated darbepoetin (50 μg/kg 24 hours before the ischemic stimulus) were studied in comparison with erythropoietin and darbepoetin in a series of experiments on male Wistar rats on a 40-minute bilateral model of renal ischemia-reperfusion. The renoprotective properties were evaluated by the results of biochemical markers of acute kidney injury, the dynamics of glomerular filtration rate and fractional sodium excretion, as well as the severity of microcirculatory disorders.Results. It was found that the prophylactic use of asialo erythropoietin (dose-dependent) and carbamylated darbepoetin leads to a decrease in the serum concentration of markers of acute renal damage, an increase in the glomerular filtration rate, a decrease in fractional sodium excretion, and a decrease in microcirculatory disorders.Conclusion. Asialo erythropoietin and carbamylated darbepoetin have the pronounced renoprotective properties and are the promising agents for the prevention and treatment of acute kidney injury.